2015
DOI: 10.3109/13697137.2015.1020482
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estradiol, progestogens, and of tibolone on breast proliferation and apoptosis

Abstract: The various progestogens can have more or less proliferative and pro-apoptotic effects than estradiol alone. Among the treatment schemes analyzed, the estradiol + dydrogesterone combination resulted in a higher apoptosis rate in relation to the proliferation rate and tibolone was associated with the lowest proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
4
0
4
Order By: Relevance
“…Some limitations of our study can be mentioned, such as the fact that we have evaluated proliferation and apoptosis with only one marker for each one, PCNA and caspase-3 respectively, although these have shown results and have already been used in previous studies such as the one by Pompei et al 17 Another limiting factor was our relatively small number of animals in the different groups. A larger sample would probably show statistical significance in other parameters that in the graphic analysis seem to be different among groups.…”
Section: Discussionmentioning
confidence: 99%
“…Some limitations of our study can be mentioned, such as the fact that we have evaluated proliferation and apoptosis with only one marker for each one, PCNA and caspase-3 respectively, although these have shown results and have already been used in previous studies such as the one by Pompei et al 17 Another limiting factor was our relatively small number of animals in the different groups. A larger sample would probably show statistical significance in other parameters that in the graphic analysis seem to be different among groups.…”
Section: Discussionmentioning
confidence: 99%
“…The roles of cortisol and testosterone in the induction of Bax-dependent apoptosis has been addressed in previous studies. In addition, progesterone has been shown to induce apoptosis in cervical, ovarian, and colon cancer cells through the Bax-dependent pathway (29,(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, T inhibits the enzyme sulphatase, which reduces the desolfatation of estrone (E3) sulfate and blocks cell proliferation in the breast, stimulating apoptosis [16]. T was associated with the least breast epithelial proliferation (evaluated by proliferating cell nuclear antigen immunohistochemistry), but also the least apoptosis (by caspase-3 immunohistochemistry) in comparison to other EP treatments [17]. Several studies have also shown a reduction in breast density during T treatment, in contrast with 'typical' E-only or EP HTs [18,19].…”
Section: 'Progestin-free' Treatmentsmentioning
confidence: 99%